(untitled) (Third Sector Social Economic Review, 2026)
This study examines the relationship between credit and economic growth using monthly data covering 2005:01-2025:08. This paper uses money supply as the control variable and estimations were performed using ARDL and NARDL approaches. Before estimating the models, it was verified that the variables were stationary at first difference stationary and that the models have cointegration relations. Moreover, it was detected that the assumptions were met, and asymmetric relationships were detected for the NARDL models. Credit growth does not have a significant effect on economic expansion with respect to ARDL models. According to the NARDL model, positive credit shocks have a positive effect on growth, while negative credit shocks have no effect on growth. Based on these findings, the impact of credit volume on economic growth appears to be asymmetric. Accordingly, policymakers examining the relationship between credit volume and economic growth should take potential nonlinear dynamics into account. This study contributes to the existing literature in three different ways. Firstly, credit and money supply are adjusted to remove inflationary effects. Secondly, the impacts of economic shocks from 2008 and Covid-19 are included and controlled in the model. Thirdly, the analyses are carried out from both symmetric and asymmetric perspectives.